Pengaruh Jaminan Sosial,Disiplin Kerja,Motivasi Kerja Terhadap Kinerja Pegawai (Pada Badan Perencanaan Pembangunan Daerah Tulungagung) - Sultan Muhammad Maftuh; Hadi Sunaryo; M. Khoirul ABS (E-JRM : Elektronik Jurnal Riset Manajemen, 2020)
ABSTRACTThe purpose of this study was to determine the effect of social security, work discipline, and work motivation on employee performance at the Tulungagung regional development planning agency. This research uses a quantitative type. The data used in this study use primary data obtained directly from respondents in the Tulungagung regional development planning agency. Data were taken from 78 (seventy eight) respondents who are employees of regional development planning agencies.This study used analysis tools in the form of validity, reliability, normality test, multiple linear regression, multicollinity test, heteroscedasticity test, F test, and t test and measured using a Likert scale. Where the results of the analysis depend on the scores obtained from respondents.The results of this study are (1) social security has a positive and significant effect on employee performance at the Tulungagung regional development planning agency (2) Work discipline has a negative and not insignificant effect on employee performance at Bappeda Tulungagung (3) work motivation has a positive and significant effect on employee performance. at the Tulungagung regional development planning agency. Keywords : Social Security, Work Discipline, Work Motivations, Performance.